2011
DOI: 10.3945/ajcn.110.000950
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake patterns are reflected in metabolomic profiles: potential role in dietary assessment studies

Abstract: Habitual dietary patterns are shown in metabolomic data. This approach successfully identified potential biomarkers of red-meat and vegetable intakes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
213
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(216 citation statements)
references
References 34 publications
3
213
0
Order By: Relevance
“…Likewise, in the LFD group, a moderate association (r>0.4, p<0.05) was found with reported red meat intake from the FFQ for histidine, 3-MH and carnosine. Some studies exhibited metabolites being discriminant among lactovegetarian and omnivorous people, showing a decreased excretion of them in people following vegetarian diets, while an increase of N-Ac, citrate, glycine and PAGN is evidenced (18,19) in vegetarian diets. Similarly, a moderate association (r>0.3, p<0.05) was found with some MD-associated metabolites (3-HB, leucine, isobutyric, 2-oxoisovaleric acid, N-Ac, proline, glycine p-cresol and PAGN) with vegetable, legume and fruit intake in MD groups from the FFQ.…”
Section: Food Intake Metabolites (Food Metabolome) Particular For Eacmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, in the LFD group, a moderate association (r>0.4, p<0.05) was found with reported red meat intake from the FFQ for histidine, 3-MH and carnosine. Some studies exhibited metabolites being discriminant among lactovegetarian and omnivorous people, showing a decreased excretion of them in people following vegetarian diets, while an increase of N-Ac, citrate, glycine and PAGN is evidenced (18,19) in vegetarian diets. Similarly, a moderate association (r>0.3, p<0.05) was found with some MD-associated metabolites (3-HB, leucine, isobutyric, 2-oxoisovaleric acid, N-Ac, proline, glycine p-cresol and PAGN) with vegetable, legume and fruit intake in MD groups from the FFQ.…”
Section: Food Intake Metabolites (Food Metabolome) Particular For Eacmentioning
confidence: 99%
“…For instance, population-based studies have shown marked differences in metabolic profiles within and between populations that reflect dietary differences (16,17). A number of metabolic profiling studies have been undertaken to assess the metabolic phenotype of humans due to their dietary pattern (18,19). Moreover, a metabolomic approach has been proposed to evaluate the intricate relationship between nutrition and health (20).…”
Section: Introductionmentioning
confidence: 99%
“…In a few other studies, TMAO levels in urine and plasma have also been associated 476 with intake of red meat, egg and dairy food (29,32,42,43 Table 7 for details on statistical results. T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 T0 T2 T24 W1 W2 W3 W1 W2 W3 W1 W2 W3 W1 W2 W3 A B…”
mentioning
confidence: 99%
“…The concept of identifying biomarkers using dietary patterns in combination with metabolomic patterns was pioneered in our research group (71) . Since then, this approach has been used in a number of studies (72)(73)(74)(75)(76) , where patterns of intake are related to metabolomic patterns (2) .…”
Section: Use Of Dietary Patterns To Identify Biomarkers Of Intakementioning
confidence: 99%